The Thermal Stability of Carbon Materials in the Air: Quantitative Structural Investigation of Thermal Stability of Carbon Materials in Air - Sádovská, Galina; Honcová, Pavla; Moravkova, Jaroslava; Jirka, Ivan; Vorokhta, Maryna; Pilař, Radim; Rathouský, Jiří; Kaucký, Dalibor; Mikysková, Eliška; Sazama, Petr (Pergamon-Elsevier Science Ltd., 2023)
The variability of the nanostructure of carbon materials results in a uniquely wide range of physical and chemical properties. This work analyses how the nanostructure affects the thermal stability of 2D and 3D graphene-based materials (graphene, fullerenes, nanotubes, zeolite-templated carbon), disordered and 3D ordered mesoporous carbon materials (activated carbons, CMK-3, 3DOMM), and layered carbon materials (few-layer graphene, graphene nanoplatelets, graphite) in the air. Combination of structural, thermogravimetric and calorimetric analyses under identical conditions for all the carbon nanomaterials showed that the most decisive factor increasing the stability is the stacking of graphene layers with long-range order parallel to each other, increasing the onset oxidation temperature (Ton) with the number of graphene layers from 530 degrees C for graphene up to 800 degrees C for graphite. The unsaturated carbon atoms at the defects and edges and the bending stress in the 3D graphene layers cause that graphene, the 3D non-defective monolayer in fullerenes and the defective monolayer in zeolite-templated carbon exhibit similar stability to disordered amorphous materials, as well as 3D organised meso-porous materials. All these materials are oxidized in a narrow Ton interval from 485 to 530 degrees C. The most sig-nificant factor for reducing the stability is the presence of specific oxygen-containing functional groups, which decrease Ton for materials with oxidized edges and with predominant hydroxyl groups by up to 150 degrees C. The relationships between the carbon structure and its stability in the air facilitate targeting the nanostructure of carbon materials in relation to their stability.
Tepelná stabilita nanostrukturních uhlíkových materiálů na vzduchu: Kvantitativní stanovení a rozhodující strukturní parametry
Keywords: Nanostructured Carbon Materials; Carbon Nanomaterials; Oxidation; Structure -stability Relationship; Differential Scanning Calorimetry (DSC); Thermogravimetric Analysis (TG); Nanostrukturované uhlíkové materiály; Uhlíkové nanomateriály; Oxidace; Struktura a stabilita; Diferenciální skenovací kalorimetrie (DSC); Termogravimetrická analýza (TG)